ChemInform Abstract: Five‐Membered 2, 3‐Dioxo Heterocycles. Part 88. Reaction of 3‐Aroylpyrrolo[1, 2‐d][1, 4]benzoxazine‐1, 2, 4(4H)‐triones with N, N′‐Dicyclohexylcarbodiimide under Thermolysis Conditions. Issue 10 (7th March 2013) - Maslivets, V. A.; Maslivets, A. N.
Abstract On heating, title compounds (I) undergo intermediate generation of ketenes (II) which react as dienes in [4+2] cycloaddition to the C=N bond of (III) with formation of benzoxazinones (IV).